Sound Biting Conspiracy: From India with "Love Jihad" - Frøystad, Kathinka (Religions, 2021)
Since 2013, India has seen a remarkable growth of a conspiracy theory known as "love jihad", which holds that Muslim men conspire to lure Hindu women for marriage to alter India’s religious demography as part of a political takeover strategy. While earlier scholarship on "love jihad" emphasizes the Hindu nationalist propagation of this conspiracy theory, this article pays equal attention to its appeal among conservative Hindus. Making its point of departure in the generative effects of speech, it argues that the "love jihad" neologism performs two logical operations simultaneously. Firstly, it fuses the long-standing Hindu anxiety about daughters marrying against their parents’ will, with the equally long-standing anxiety about unfavorable religious demographic trends. Secondly, it attributes a sinister political takeover intent to every Muslim man who casts his eyes on a young Hindu woman. To bring out these points, this article pays equal empirical attention to marriage and kinship practices as to the genealogy of, and forerunners to, the "love jihad" neologism, and develops the concept of "sound biting" to bring out its meaning-making effect.